MEN IN LANGUAGE TEACHING TO CHILDREN - Marcos Moreira dos Santos, Robert (Revista Gênero e Interdisciplinaridade, 2023)
This study was born from the need to address a subject that has gained more and more space in the school environment, however, little has actually been discussed about it. It is understood that the presence of male teachers working in language teaching and in the initial grades is still something new for most of society, which is why this discussion is so necessary. In this way, we seek to take a small step towards the so-called equality that is preached and not lived. So, the general objective of this study is to verify how the choice to work in basic education can generate problems for the man who starts his career in teaching. How far can social prejudice harm those who decide to pursue a career in teaching. The methodology chosen to carry out this study is bibliographical research, in which the bases to guide this work were sought in the existing literature. It is concluded that much still needs to be done so that men can actually gain recognition and space within the school environment for their performance as professionals and not just for their gender.